Óleos essenciais de alecrim-pimenta e capim citronela no controle da antracnose da goiaba - Souza, Talytha Ravenna de Melo (2021)
The main postharvest disease of guava in Brazil is anthracnose, which requires efficient control and has a low economic, social and environmental impact. Therefore, this study aimed to evaluate the inhibition potential of rosemary pepper and citronella grass essential oils on the in vitro and in vivo control of Colletotrichum sp. on guava. The in vitro experiment was carried out using Petri dishes 5 cm in diameter using potato-dextrose (BD) medium added with several combinations of essential oils (5 mL of BD medium + 5 mL of treatments). The design used was completely randomized (CDR), consisting of 16 treatments (T1-T16), with 4 replications, each repeated in a Petri dish. The plates were placed in a growth room at a temperature of 27 °C ± 2 °C, under a 12 h photoperiod. The evaluations were carried out on the seventh day with the weighing of fungal colonies and the image analysis of mycelial growth, which were analyzed by analysis of variance and compared by the Scott_Knott test at a 5% probability level. The in vivo experiments were used, testing six guava fruits giving inhibitory efficiency on the fungus and no in vitro experiments were statistically different from each other (T7, T9, T10, T11, T12, T13 and the Control). The experiment was carried out in CRD, in a factorial scheme, with seven treatments, 2 control methods (curative and preventive) and 3 repetitions. Each experimental unit consisted of two fruits. The analyzes were carried out for 12 days with intervals of 1 day between each evaluation, observing the disease progress and the percentage of infection of the fruits. Data were analysed in the SISVAR statistical program. Values over time were submitted to regression analysis. The values of the percentage of severity were analyzed using the analysis of variance and compared by the Scott-Knott test at the 5% probability level. Essential oils of rosemary pepper and citronella dissipation effect on total and partial inhibition of mycelial growth of Colletotrichum sp., causal agent of anthracnose in guava. The fruits treated with essential oils obtained a reduction without a percentage of severity, the most promising treatment being the one that used the essentials in the combined form in the rosemary-pepper practices - 1 mL. L-¹; citronella - 0.5 ml. L-¹, both in the curative and preventive method.